Natural Truffle Peels for Effective Removal of Rhodamine B Dye from Aqueous Solutions - Alshaikh, Hind Abdullah; Saigl, Zainab Mohammad (Indonesian Journal of Chemistry, 2026)
This study evaluated truffle peel powder (TPs) as a sustainable biosorbent for removing Rhodamine B (RB) dye from aqueous solutions and real samples. TPs were characterized by FTIR, SEM, and EDX, revealing functional groups and porous surfaces favorable for adsorption. The adsorption process followed the Langmuir isotherm (R2 = 0.9969) with a maximum capacity of 0.0833 mg/g at 25 °C, confirming monolayer adsorption. Kinetics fit the pseudo-second-order model (R2 = 0.9981), indicating chemisorption. Thermodynamic analysis showed the removal process is spontaneous and exothermic (ΔH = −26.06 kJ/mol; ΔG = −4.00 kJ/mol; ΔS = −74.03 J/mol K), involving reduced randomness at the interface. The method achieved good recovery in various matrices, such as ice pop, seawater, bottled water, and tap water. Results demonstrate that truffle waste offers an effective, eco-friendly solution for dye-contaminated water, combining strong adsorption performance with environmental sustainability.